Developing Problem-Based Speaking Assessment Of High Order Thinking Skills Implementation For Asd Students - Tiyas Saputri (Universitas Muhammadiyah Surabaya, 2019)
In Indonesia, 2013 curriculum is the newest curriculum used after having some transformations. The implementation of 2013 curriculum is not an easy thing because the teacher has to understand well about it. High Order Thinking Skill (HOTS) implementation is mandated by the scientific-based 2013 national curriculum in Indonesia. It means that HOTS is one of the aspects in the 2013 curriculum that must be implemented. This must also be implemented to Autism Spectrum Disorder (ASD) students. ASD students are students with a lifelong biological disorder with a wide range of appearances. To implement HOTS, the ASD students had to be guided intensively by the teacher to think critically and creatively. However, most of the teachers got problems to develop the assessment that could stimulate ASD students’ critical thinking and creativity. This study aims to develop problem based speaking assessment of HOTS implementation to stimulate ASD students’ critical thinking and creativity. In this research, Research and Development approach was employed with the second grade ASD students of Yamastho primary school in the academic year of 2018/2019 as subject. The data collection instruments were a questionnaire, interview, observation checklist, and test. The researcher collaborated with the teacher to develop this assessment. The ASD students’ score speaking skill improvement was 60.33 to 75.33, critical thinking skill was 61.33 to 74.33 and creativity skill was 62.67 to 75.33. To know the significance of the research, the researcher used SPSS. The results indicated that there was a significant difference between the result of pre-test and post-test. In other words, there is a significant improvement in the ASD students’ speaking, critical thinking, and creativity skill after they used this assessment.Keywords: ASD, HOTS, Problem-based Speaking Assessment, Critical Thinking, Creativity